Sparking the #MeToo revolution in India: The "Nirbhaya" case in Delhi - Aparna Mathur; Abdul Munasib; Devesh Roy; Akshay Bhatnagar (American Enterprise Institute (AEI), 2019)
In 2012, anger erupted on the streets of Delhi following the violent rape and murder of a young woman. The scale of the protests, the extent of the media coverage, and the intensity of the public's opprobrium of the police and the administration of Delhi, was unprecedented. This paper argues that these events had a measurable impact on the reporting of crimes against women – rape and other sexual assaults – in Delhi.
Keywords: A; 330; India; sexual harassment; Crime; rape